Zimbabwean communication agencies - Anna Oksiutycz; Abyshey Nhedzi (Communicare)
Researchers from various countries have studied the practices of communication industries worldwide. Despite this nexus of study, relatively little research has been done on the practice of communication in Zimbabwe. In order to contribute to the understanding of the state of the communication industry on the African continent, this study reports on the results of a survey of 50 Zimbabwean communication agencies. This article is different from other studies on the communication industry because it focuses at an institutional level across the agencies, rather than at the level of individual practitioners. The findings focus on four main topics, namely practitioner profile, agency profile, prevailing professional practices and practitioners’ views on future industry trends. The research indicates that the Zimbabwean communication industry is vibrant despite the economic and political challenges facing the country. Owing to economic challenges and stiff competition, most agencies are multipurpose in nature and provide a wide variety of communication and creative services to their clients. The agencies provide services such as advertising, graphic design, branding, website development, event management, video production, online marketing, media relations, mobile app development, and even animation. There is a growing trend to use digital platforms of communication, yet radio and print (magazines and newspapers) remain essential communication channels. Among social media platforms, Twitter, Facebook and YouTube are the most used by practitioners in Zimbabwe, while online audio-podcasts, blogging sites, crowdsourcing and Linked-in are less popular. Practical issues are addressed regarding information about how agencies have adapted (or can adapt) to the new ways of strategic practice with clients in order to keep up with the changing Zimbabwean market. This research also provides valuable insights into the communication industry as a whole. It explores possible opportunities and threats for communication practitioners presented by economic and political environment issues and suggests directions for further research in this area.